Development of magnetic solid phase extraction based on magnetic chitosan–graphene oxide nanoparticles and deep eutectic solvents for the determination of flavonoids by high performance liquid chromatography. Issue 48 (26th November 2021) - Jafari, Zahra; Hadjmohammadi, Mohammad Reza
Abstract : Fe3 O4 –CS–GO–MSPE-DES was used for the extraction and determination of some flavonoids. CS–GO was synthesized and immobilized on the inner surface of Fe3 O4 . The method can be directly used in relatively complicated samples. The method is effective, sensitive and has wide LDRs. Abstract : An environmentally friendly magnetic solid phase extraction method was developed based on magnetic chitosan–graphene oxide nanoparticles and deep eutectic solvents (DESs) for the pre-concentration and isolation of flavonoids (apigenin, morin, naringenin, and quercetin) of natural orange juice, commercial apple juice, onion juice, green tea, and natural apple juice samples. DESs via hydrophilic and π–π interactions could increase the extraction performance. The immobilization of chitosan–graphene oxide on the surface of Fe3 O4 nanoparticles improved their chemical properties and mechanical stability. In addition, the prepared magnetic nanoparticles with the hydrophilic polymeric network and the high surface area of the graphene oxide increased the access of binding sites and extraction performance. The use of DESs as desorption of solvent and the individual properties of MANPs provided the ability for high extraction recovery and accelerates the time to reach equilibrium. The principal variables that influence microextraction efficiency, including the extraction time, type of DES, stirring rate, desorption time, type of eluent solvent, and pH of the sample solution, were screened via the Plackett–Burman design and then the variables were optimized by the Box–Behnken design. Under the optimum conditions obtained, the developed method showed a good working range ( R 2 ≥ 0.9962). The limit of detection (LOD) and the limit of quantification (LOQ) ranged from 0.03 μg L −1 (morin) to 0.14 μg L −1 (naringenin) and from 0.09 μg L −1 (morin) to 0.46 μg L −1 (naringenin) variables, respectively. The intraday precision was in the range of 4.1–4.8. In order to experiment with the precision and applicability of the MSPE-DES method, spiking recovery studies were performed in beverages and vegetable samples (natural orange juice, onion juice, commercial apple juice, natural apple juice, and green tea). The recovery results for real samples were calculated as 90–102%.